2006
DOI: 10.1097/01.moh.0000239704.17427.9b
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin resistance: is this term meaningful?

Abstract: Given the multifactorial nature of atherothrombosis, recurrence of cardiovascular events in aspirin-treated patients does not necessarily suggest 'drug failure'. A cause-effect relationship between platelet insensitivity to aspirin and cardiovascular recurrence has not been defined overall because aspirin compliance has been scarcely considered. Until this information is taken into account, the existence of 'clinical resistance' to aspirin should be reconsidered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…These results are consistent with a recent publication that showed inadequate platelet inhibition in only 4.2% of patient on ASA versus 50.9% of patients on clopidogrel, despite their use of a more lenient cut off for P2Y12 of ≤40% 5 . The fact that our study and others have shown significantly higher proportion of patients on ASA with adequate platelet inhibition may be relate to the fact that only 75 mg of aspirin is required to reach almost complete irreversible inhibition of the cyclooxygenase in nearly every patient 6–8 . However, comparing ASA to clopidogrel may not be valid since each one of them expresses its antiplatelet effect on different platelet receptors.…”
Section: Discussionsupporting
confidence: 86%
“…These results are consistent with a recent publication that showed inadequate platelet inhibition in only 4.2% of patient on ASA versus 50.9% of patients on clopidogrel, despite their use of a more lenient cut off for P2Y12 of ≤40% 5 . The fact that our study and others have shown significantly higher proportion of patients on ASA with adequate platelet inhibition may be relate to the fact that only 75 mg of aspirin is required to reach almost complete irreversible inhibition of the cyclooxygenase in nearly every patient 6–8 . However, comparing ASA to clopidogrel may not be valid since each one of them expresses its antiplatelet effect on different platelet receptors.…”
Section: Discussionsupporting
confidence: 86%
“…Drug non-adherence in patients who claim to have taken aspirin has received considerable attention recently [12,13,17,18,23]. Measurements of salicylate levels in the blood do not circumvent this problem [24].…”
Section: Discussionmentioning
confidence: 99%
“…While compliance has been shown to be a major factor in non‐response to aspirin, it cannot account for the postoperative effect observed in this patient cohort, all of whom were all prescribed aspirin in the perioperative and postoperative periods [36]. AA‐induced platelet aggregation, as used in this study, is believed to be the most appropriate means of assessing aspirin non‐response [37]; however, it may not be sensitive enough to fully exclude a persistent production of thromboxane A 2 because of incomplete inhibition of COX‐1[36]. Serum thromboxane levels were not measured in this study.…”
Section: Discussionmentioning
confidence: 99%